Influence of cloudiness on the incident shortwave radiation of Nevado Coropuna - Ramos, Isabel (2018)
The main objective of this work is to analyze the influence of cloud cover on shortwave radiation incident of the Nevado Coropuna during 2015-2016. In this presentation they propose to discuss that Arequipa, during the day, has more clouds between December to March above 80%. At night the cloudiness diminish significantly, hourly there are more clouds in the afternoon. The NC has a similar pattern, and there is a difference among the oriental and occidental side. Also, propose the cloudiness radiation has a high impact in the incident shortwave, in clear moments the radiation could reach 1200 W/m2, meanwhile with cloudiness this does not pass the 600 W/m2. In the dry period, generally there are not clouds; in the conventional meteorological stations are found predominantly high clouds, cirrus.